Innovative Marketing Strategies in the Digital Era: Systematic Literature Review Analysis - Nadeak, Thomas; Rahayu, Agus; Hendrayati, Heny (West Science Social and Humanities Studies, 2024)
Running a business in the modern era is different from business in the past. Business today is greatly influenced by technological advances, for those who master the touch of technology in marketing, they are the ones who can market products, especially in the current digital era. This research aims to gain an understanding of marketing strategies in the digital era. For this reason, we reviewed several studies that we obtained with evidence that we examined from various sources, including scientific papers, especially marketing strategies. Based on the analyzed data and discussion, it can be concluded that online marketing is successful by following the right steps for digital media, mapping marketing, choosing appropriate digital media, and implementing all internet-based marketing activities. Consumers are adopting an increasingly active role in co-creating marketing with their respective companies and brands. In turn, companies and organizations are looking to online social marketing programs and campaigns in an effort to reach consumers where they 'live' online. However, the challenge many companies face is that although they recognize the need to be active on social media, they do not really understand how to do it effectively, what performance indicators they should measure, and how they should measure it. Furthermore, as companies develop social media strategies, platforms such as YouTube, Facebook, and Twitter are too often treated as stand-alone elements rather than as part of an integrated system. This article offers a systematic way to understand and conceptualize online social media, as an ecosystem of related elements involving digital and traditional media. We highlight best practice case studies from organizations' successful efforts to leverage social media to reach important young consumer audiences. Then, we conclude with some insights and lessons related to the strategic integration of social media into a company's marketing communications strategy. The internet has brought disruptive changes to the business landscape through the creation of a number of digital marketing tactics. However, with these new tactical options, marketing managers need to (1) prioritize what they want to achieve and (2) determine which digital marketing tactics to invest in. In this article, we consider these issues from the perspective of four business strategies: explorer, analyzer, low-cost defender, and differentiated defender. In this article, we provide marketing managers with insight into how businesses pursuing various strategies approach these digital marketing issues, with the ultimate goal of assisting managers in the efficient and effective implementation of their corporate strategies.